Impact of T-inversion on the outcome of Takotsubo syndrome as compared to acute coronary syndrome - Gietzen, Thorsten; El-Battrawy, Ibrahim; Lang, Siegfried; Zhou, Xiao-Bo; Ansari, Uzair; Behnes, Michael; Borggrefe, Martin; Akın, Ibrahim (European journal of clinical investigation, 2019)
Background Previous studies revealed that patients with Takotsubo syndrome (TTS) have a higher mortality rate than the general population and a comparable mortality to acute coronary syndrome (ACS). Repolarisation abnormalities, namely T-wave amplitude, may provide incremental prognostic information, in addition to traditional risk factors in ACS. This study was performed to determine the short- and long-term prognostic impact of inverted T-waves in TTS patients, as compared to ACS patients. Methods and results Our institutional database constituted a collective of 138 patients diagnosed with TTS from 2003 to 2017, as well as 532 patients suffering from ACS. Patients with TTS or with ACS (n = 138 per group) were matched for age and sex and assessed retrospectively and prospectively and divided into two groups, TTS with inverted T-waves (n = 123) and ACS with inverted T-waves (n = 80). In-hospital complications such as respiratory failure with the need of respiratory support (60.2% vs 6.3%; P < 0.01), thromboembolic events (13.8% vs 2.5%; P < 0.01) and cardiogenic shock (18.9% vs 8.8%; P = 0.05) were significantly more presented in TTS as compared to ACS patients. Among cardiovascular risk factors diabetes mellitus (23.6% vs 45.0%; P < 0.01) and arterial hypertension (57.7% vs 78.8%; P < 0.01) were more presented in ACS patients as compared to TTS patients. Short-term mortality was similar, however the long-term mortality of 5 years was significantly higher in the TTS group (25.2% vs 7.5%; P < 0.01). In univariate analysis were male gender, EF < 35%, GFR < 60 mL/min, cardiogenic shock, inotropic drugs and history of cancer predictors of 5-year mortality. The multivariate analysis showed only male gender (HR 2.7, 95% CI 1.1-6.5; P = 0.02), GFR < 60 mL/min (HR 2.8, 95% CI 1.2-6.0; P = 0.01) and history of cancer (HR 3.6, 95% CI 1.4-9.3; P < 0.01) as independent predictors of 5-year mortality. Conclusion Rates of long-term mortality were significantly higher in TTS patients showing inverted T-waves compared with patients diagnosed with ACS with inverted T-waves. However, T-inversion was not an independent predictor of 5-year mortality in the multivariate analysis.